Experiment on Application of Laser Obscuration for Counting and Sizing of Spherical Fuel Particle - Suwardi Suwardi (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2012)
The paper reports an experiment on application of laser obscuration for counting and sizing of spherical particle fuel. It is a part of design study on counting and measuring device for particle fuel. The measurement is based on monitoring of sheet shaped laser beam obscuration caused by particles passage. Laser generate a parallel and thin beam laser perpendicularly crossing the particles stream at a point which is specifically windowed. A photo detector is placed -side by side- the laser relative to the particles passage for monitoring the laser beam. The detector is connected to an oscilloscope for signal measurement and display. The typical diameter bare particle is 500 um; while of coated particles is 1300 um, so a beam of 30 um thickness has been chosen. The particles were dropped one by one into a vertical tube which crosses the laser beam at windowed portion. The progress of obscuration reflects the form of particle projection on a plane permits the construction of size and sphericity of particle. The design has been realized and a measurement function has been demonstrated. The display of detected laser beam showed the passage of particle as a parabolic curve as prediction. It was suggested to record the laser obscuration on a micro computer via DAQ and to develop a computer program for counting and sizing the spherical particle. Keywords:spherical particle, nuclear fuel, size, shape, laser beam, obscuration